Regulatory and legal regulation of hydraulic structures and their impact on water safety of the Republic of Kazakhstan. - Muztauov, Жандос; Gavrilova, Юлия; Umarov, Дилшод (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article discusses the issues of regulatory regulation and control of hydraulic structures (hereinafter referred to as GTS), as well as the current system of public administration. The purpose is to identify the problems of legal regulation of ensuring the safe management of GTS and to develop proposals for improving the current legislation and the mechanism of state regulation. To achieve this goal, it is necessary to solve the following tasks: - to determine the regulatory framework governing the system for ensuring the safe operation of GTS; - to identify responsible state bodies whose powers include the implementation of state policy in the field of water management, including regulation and control over the activities of GTS owners; - to identify conflicts in the norms of national law that impede the safe operation of GTS and problems of public administration in the field of GTS. The GTS is a complex mechanism that performs several tasks simultaneously to meet the needs of the country's economy and population. Consequently, the GTS system needs not only clear legislative regulation, but also effective public management. Every year, the state spends billions of budget funds within the framework of national projects and state programs aimed at reforming the GTS system, which currently represents materially worn-out water management facilities erected during the Soviet era. Currently, there are about 1,700 GTS in Kazakhstan, which, instead of developing the country's energy and agriculture sectors, are a burden on the country's budget. The lack of proper state control over the activities of GTS owners, combined with the lack of clear legislative regulation, creates a risk of emergency situations that can negatively affect the ecosystem of the region, as well as hydropower and irrigation in general. The results of the study made it possible to identify current problems of a legislative nature, the public administration system and develop proposals for their solution.